CARDIOVASCULAR RISK IN PATIENTS WITH EARLY RHEUMATOID ARTHRITIS BEFORE DISEASE-MODIFYING ANTIRHEUMATIC THERAPY (PRELIMINARY DATA OF THE REMARCА STUDY) - Yu. N. Gorbunova; D. S. Novikova; T. V. Popkova; E. I. Markelova; Yu. O. Korsakova; O. A. Fomicheva; D. S. Kolmakova; E. L. Luchikhina; D. E. Karateev; A. V. Smirnov; E. L. Nasonov (Научно-практическая ревматология, 2014)
Objective: to estimate the level of cardiovascular risk in patients with early rheumatoid arthritis (RA) before therapy with disease-modifying antirheumatic drugs (DMARDs).Subjects and methods: Seventy-three patients with early RA who had not previously taken DMARDs or glucocorticoids were examined. Disease activity was assessed by the DAS28, SDAI, and CDAI. All the patients were examined by a cardiologist. The investigators assessed traditional risk factors (RF), by determining the overall coronary risk according tothe modified SCORE scale, the degree of a risk for cardiovascular events (CVE), carried out 24-hour ECG and blood pressure monitoring, echocardiography (EchoCG), and carotid duplex scanning, identified coronary artery calcification by multislice spiral computed tomography, and, if indicated, performed stress EchoCG and coronary angiography.Results. The diagnosis of coronary heart disease was established in 13 patients. NYHA functional class I or II chronic heart failure (HF) was diagnosed in 8 patients, systolic HF in 2, HF with preserved left ventricular ejection fraction in 6 cases. There was left ventricular hypertrophy in 22 (30.1%) patients, carotid atherosclerotic plaques in 26 (35.6%), coronary artery calcification in 30 (41.1%), hypertension in 38 (52.1%), abdominal obesity in 34 (46.6%), dyslipidemia in 40 (54.8%), hypercholesterolemia in 37 (50.7%), hypoalphalipoproteinemia in 21 (28.8%), hypertriglyceridemia in 12 (16.4%), low physical activity in 30 (41.1%), and smoking in 13 (17.8%). Thirty-three of 53 women weremenopausal. Fasting hyperglycemia was found in 11 (15.1%) patients; type 2 diabetes mellitus in 4 (5.5%). Thirty-one (42.5%) patients had at least three RFs. In accordance with the current classification of the degree of cardiovascular risk, very high, high, moderate, and low risks for CVE were observed in 58, 8, 8, and 26% of the RA patients, respectively.Conclusion. Most rheumatoid factor- and anticyclic citrullinated peptide-positive patients with early RA and high disease activity have high and very high cardiovascular risks.